Efficacy of psychoeducation on symptomatic and functional recovery in bipolar disorder. (4th September 2012) - de Barros Pellegrinelli, K.; de O. Costa, L. F.; Silval, K. I. D.; Dias, V. V.; Roso, M. C.; Bandeira, M.; Colom, F.; Moreno, R. A.
<x xml:space="preserve">Abstract</x> Objective: To evaluate the efficacy of psychoeducation in the symptomatic and functional recovery, and quality of life (QoL) in a sample of patients with bipolar disorder (BD). Method: The sample comprised 55 patients with BD I and II in remission (Young Mania Rating Scale ≤6 and Hamilton Depression Rating Scale ≤7). Out‐patients were matched assigned to receive 16 sessions of psychoeducation [experimental group (EG)] or 16 sessions of placebo without psychoeducation [control group (CG)]. Groups were evaluated at study baseline, midpoint, endpoint, and at 6‐ and 12‐month follow‐ups. Results: No significant differences between the groups were found for the variables evaluated (mood symptoms, functioning and QoL), except for overall clinical improvement, subjectively perceived by EG subjects. Both groups showed a trend toward improved clinical global impression and QoL (environmental). No reduction in mood symptoms or improvement in psychosocial functioning was observed. Psychosocial treatment compliance was positively correlated with global functioning, social adjustment, sociability, and global clinical impression. Conclusion: Sixteen session psychoeducation seems to be ineffective to prevent mood episodes or improve functioning in a sample of bipolar patients.